VARIABILITY OF SEDIMENT TRANSPORT IN THE SCOTT RIVER CATCHMENT (SVALBARD) DURING THE HYDROLOGICALLY ACTIVE SEASON OF 2009 - Kociuba, Waldemar; Janicki, Grzegorz; Siwek, Krzysztof (Quaestiones Geographicae, 2014)
Investigations of fluvial transport in the glacial river catchment (Scott River, Spitsbergen) were conducted in the melt season of 2009. A special attention was given to dynamics and distribution of bedload transport − the major component of fluvial transport in a proglacial gravel-bed river. Bed-load transport rate was determined using the River Bedload Traps (RBT) constructed for the project’s need. The obtained results indicate high diversity of bedload transport, the amount of which reached up to 220 kg m-1 day-1 for twenty-four hours in particular measurement sites. The results confirmed also great variability of local intensity fluvial processes in polar zone.